Supporting knowledge sharing in a community with divergence - Díaz, Alicia Viviana (^p Datos electrónicos ( 58 KB))
In this paper, we propose a technological approach that allows communities to coexist with conflicts and leaves that agreed knowledge emerges naturally, by the simple act of sharing knowledge. On the top of a collaborative workspace for developing a shared knowledge repository, we put forward: a mechanism for maintaining the discussion threads, a knowledge awareness mechanism to be up-to-date about discussion threads and their evolution, and a user centred workspace to support personal view of the shared repository with the capability of adding private knowledge. -- Keywords: Knowledge Sharing. Discussion Threads, Groupware, Knowledge Awareness.